Structural Changes in Polyethylene Terephthalate (PET) Waste Materials Caused by Pyrolysis and CO Activation - José B. Parra; Conchi O. Ania; Ana Arenillas; Fernando Rubiera; José J. Pis; José M. Palacios (Adsorption Science & Technology)
For ecological reasons, there is an increasing demand for recycling polyethylene terephthalate (PET) wastes in developed countries. Although one potential application might be its utilisation for the production of activated carbons, the behaviour of these wastes when subjected to different heat treatments and activation processes is still not very well known. In the present work, samples with different degrees of burn-off were prepared by pyrolysis in an inert atmosphere and subsequent CO 2 activation at high temperatures. The derived changes in the textural and structural properties of the residual solids were studied by helium picnometry, N 2 and CO 2 adsorption isotherms, powder XRD, Raman spectroscopy and XPS. The study reveals that CO 2 activation of PET wastes develops a carbonaceous matrix with micropores. Helium measurements showed that the mass density of the activated samples increased as the degree of burn-off increased. Characterisation studies revealed that the structural changes derived from pyrolysis and further CO 2 activation mostly involved a progressive decrease in the number of structural units.